Pengaruh Kombinasi Fermentasi Limbah Cair Tahu dan NPK Terhadap Pertumbuhan dan Hasil Selada ( Lactuca sativa L.) Varietas Grand Rapids Pada Sistem Vertikultur - Nikken Dwiayu Sugianti Miharja; Sulistyo Sidik Purnomo; Tatang Surjana (Peneliti.net, 2021)
This research was carried out in July-September 2021 in the experimental field in Panyingkiran Village, Pabuaran District, Subang Regency, West Java. The research method used is an experimental method using a Randomized Block Design consisting of 8 treatments and 5 replications so that a total of 40 experimental units with different concentrations, namely T0 control, T1= 200 ml/l of tofu liquid waste fermented and 150 kg/ha NPK, T2=200 ml/l of tofu liquid waste fermented and 225kg/ha NPK,T3=400 ml/l of tofu liquid waste fermented and 150 kg/ha NPK,T4=400 ml/l of tofu liquid waste fermented and 225kg/ha NPK,T5=400 ml/l of tofu liquid waste fermented and 300 kg/ha NPK,T6=600 ml/l of tofu liquid waste fermented and 150 kg/ha NPK and T7=600 ml/l of tofu liquid waste fermented and 225kg/ha NPK. The effect of the treatment was analyzed by means of variance, if the F test at 5% level was significant, then to find out the best treatment, proceed with the DMRT (Duncan Multiple Range Test) further test at a significant level of 5%. The result of this research is that the combination treatment of tofu liquid waste fermentation and NPK has a significant effect on plant height, number of leaves, leaf area and wet weight per plant. T5 treatment was able to provide the highest growth and yield of lettuce plants with a wet weight per plant of 55,49 grams.